Evaluation of serum adiponectin as a marker of insulin resistance in women with polycystic ovarian syndrome: a comparative cross-sectional study - Olugbenga Ojatokunbo Runsewe; Abiodun Adeniyi Adewunmi; Gbenga Olorunfemi; Abimbola Tawaqualit Ottun; Ayokunle Moses Olumodeji; Babalola Ogungbemile; Tamramat Iyabo Runsewe-Abiodun (BMC, 2024)
Abstract Background Insulin resistance (IR) is known to be prevalent amongst women with polycystic ovarian syndrome (PCOS). Its presence has been linked to chronic anovulation and marked long term complications in women. Hence, identification and treatment of IR in women with PCOS is required to prevent the metabolic and reproductive complications of the disease. The aim of this study is to determine if serum adiponectin could be used as a surrogate marker for insulin resistance among women with PCOS. Materials and methods A total number of 148 consenting women with PCOS diagnosed using the Rotterdam criteria were recruited for this study. Fifty-two of these women had insulin resistance were compared with 96 of the women who did not have insulin resistance. The serum Adiponectin levels, fasting blood glucose and fasting insulin levels were assayed in all study participants. Insulin resistance was assessed in all the study participants using the Homeostasis Model Assessment for Insulin Resistance (HOMA-IR). Data were analyzed using relevant inferential statistics at 95% confidence interval and p value of < 0.05. Results The prevalence of insulin resistance among the study participants was 35.1%. Majority of the women (83.1%) had a high body mass index (BMI). More than half (68.2%) of the participants were in the age range of 21-30years and 76.4% (113) were nulliparous. There was no statistically significant difference in the median adiponectin level among insulin resistant (3.735 ug/ml) and non-insulin resistant participants vs. (3.705 ug/ml) (p = 0.6762). Both univariate and multivariate regression analysis did not show a statistically significant relationship between adiponectin and insulin resistance in PCOS. Conclusion The prevalence of insulin resistance in women with PCOS is high and serum adiponectin is not a suitable surrogate marker of insulin resistance in women with PCOS.